Preoperative cognitive dysfunction in older elective noncardiac surgical patients in South Africa. (September 2020) - Amado, Leandra A.; Perrie, Helen; Scribante, Juan; Ben-Israel, Karin-Ann
Abstract: Background: Cognitive dysfunction after surgery includes delirium and postoperative cognitive dysfunction. Important risk factors for these include increased age and pre-existing cognitive dysfunction. This study describes preoperative cognitive dysfunction and its associated factors in patients aged ≥60 yr awaiting elective noncardiac surgery in a developing country. Methods: A prospective, contextual, descriptive study design with consecutive convenience sampling was used at Chris Hani Baragwanath Academic Hospital, Johannesburg, South Africa. Assessment of cognition was subjective (through casual conversation, henceforth referred to as observer assessment) and objective (using the Mini-Cog test). Results: A total of 194 outpatients (median age: 65 yr) were assessed. A score ≤3 (indicating mild cognitive impairment) was obtained by 111 patients (57.2%). Subjective memory complaints were reported by 124 patients (63.9%). Univariate analyses demonstrated significant associations between low Mini-Cog scores and increasing age (rs =−0.1901; P =0.0079), unskilled occupation ( P =0.0033), low functional status (rs =−0.1831; P =0.0106), low level of education ( P =0.0005), and frailty (rs =−0.3010; P <0.0001). Logistic regression showed level of education and frailty to be significant. A score ≤3 is more likely in frail patients (odds ratio: 7.54; P =0.003) and those with only primary school education (odds ratio: 3.54; P =0.003). Conclusions: Undiagnosed pre-existing cognitive dysfunction was common in older patients awaiting surgery at a regional academic hospital in South Africa. Patients at risk for cognitive dysfunction should be identified through brief preoperative screening.